Optimalisasi Sistem Manajemen Barang dalam Bisnis Sewa Properti melalui Implementasi Appsheet (Studi Kasus: Sewa Rumah BSB) - Krisnawan, Albertus Bima; Kurniasih, Tatit (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
BSB House Rental, a property rental enterprise situated in Kartasura Subdistrict, Sukoharjo Regency, encounters challenges in asset maintenance, notably the loss of approximately 2 items per tenant turnover. With frequent turnovers, facilities often undergo damage requiring repairs. This study aims to address these issues by developing a no-code-based asset management system using AppSheet technology. Employing a qualitative-experimental methodology, the research involves interviews with the business owner to identify challenges and prototyping the system using AppSheet. The application, designed to inventory assets and streamline replacement requests, is subjected to blackbox testing to assess its effectiveness in recording and processing item replacements.